THE IMPACT OF SEAWEED FARMING ON THE PHYTOPLANKTON COMMUNITY STRUCTURE - Parakkasi, Parman; Rani, Chair; Syamsuddin, Rajuddin; Tambaru, Rahmadi (Jurnal Ilmu Kelautan SPERMONDE, 2020)
This study was aimed to analyze the impact of seaweed farming on changes in the structure of phytoplankton communities on various ecosystems and their relationship with environmental factors. The study was conducted in May-October 2017 in the waters of Karampuang Island, Mamuju Regency. Plankton samples were collectedfromthreecultivationareas, namely areas with sandy bottom (control), seagrass beds, and coral reefs. In each area, three media were placed with a longline system, size 40 x 30 m2 (as replication). Sampling was carried out at the beginning before initiation of the cultivation and every two weeks after cultivation was started for 42 days. Phytoplankton sampling and measurement of environmental factors were carried out at fivesamplingpoints representing the cultivation areas. In sandy areas, sampling was also applied in areas outside the cultivation at a distance of 25m and 50m. Variance analysis was used to analyze differences in the species number and abundance of phytoplankton. Ecological indices was used to test phytoplankton biodiversity. PCA was used to analyze its relationship with environmental factors. Differences in the species number and abundance of phytoplankton between farming areas according to temporal scale were found. The high number and speciesabundance of phytoplankton were found in seagrass areas and significantly different from coral reefs and sandy area. Seaweed farming at the beginning of the farming period showed a positive impact by increasing the number of species and abundance of phytoplankton, but then decreased after entering Week 4-Week 6, along with the occurrence of ice-ice disease on the seaweed. Diversity index value was classified as medium with high equality without the dominance of particular species. The high number of species and abundance of phytoplankton occured at second weeks in all cultivation areas which are characterized by abundance of zooplankton with environmental characteristics, i.e. high DO and low PO4, NO3, andDOM.